SPATIAL DISTRIBUTION OF AND ANTHROPOGENIC IMPACTS ON GHOST CRAB Ocypode quadrata (CRUSTACEA, OCYPODIDAE) BURROWS IN MACEIÓ, BRAZIL - SILVA, Willian Talvane Arestides Ferreira da; CALADO, Tereza Cristina dos Santos (Revista Nordestina de Zoologia, 2011)
Human impacts on sandy beaches have increased year by year. In proof of the existence of these disturbances, several species which live in these environments function as potential bioindicators of the environmental health by oscillating the density of individuals in the population. Ghost crabs, or marias-farinhas, as they are known in Northeast Brazil, have been effectively used to measure levels of anthropic influence on their habitat. This study shows that human disturbances, e.g. recreational activities and pollution, have a great influence on the abundance of ghost crab burrows. Burrow abundance decreased considerably on the urban beach (Avenida beach) when compared with the non-urban beach (Pontal sand bar). It was also observed that burrows were randomly distributed at both beaches.